Recent advances in biomedical engineering of nano-hydroxyapatite including dentistry, cancer treatment and bone repair. (15th June 2021) - Du, Mingzu; Chen, Jingdi; Liu, Kaihua; Xing, Huaran; Song, Cui
Abstract: Hydroxyapatite (HAp) has significant biological activity, degradability, and osteoconductivity. In recent decades, it has been widely used in dentistry, anti-tumour drug carriers, and orthopaedic repair. However, hydroxyapatite has limit features which are poor mechanical properties for directly inducing tooth enamel remineralization, particle size and morphology issues on drug delivery and brittleness for bone transplantation. This article summarizes the problems encountered in the preparation, application, and modification of hydroxyapatite in the above-mentioned fields and the current research progress, combining theory with experiment. Therefore, the greatest significance of this review is to comprehensively integrate and argue the forms and effects of nHA-based biomaterials, which provides a theoretical basis for the application of this material and help readers have clear insights into future research. Graphical abstract: Image 1